ASSESSING SKILL REQUIREMENTS AND COMPENSATION STRUCTURES FOR CREW MEMBERS IN THE INDIAN AVIATION INDUSTRY - Sharma, Shubhada; Pawar, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study looks into the different skills that crew members in India's aviation industry need and whether their pay really reflects the responsibilities and risks that come with their jobs. As India's aviation industry grows quickly, new duties have been added for cabin crew, such as emergency management, technical knowledge, and mental toughness. However, concerns have been raised about whether their pay is fair, and the study uses a mix of surveys and interviews with cabin crew and HR professionals from major Indian airlines to find that there is a big difference between what they are paid and what they are expected to do. This shows that we need a more skill- and risk-based pay system to make sure that employees are happy, stay with the company, and follow global standards.